2017
DOI: 10.4103/ijd.ijd_702_16
|View full text |Cite
|
Sign up to set email alerts
|

Cortisol homeostasis in the epidermis is influenced by topical corticosteroids in patients with atopic dermatitis

Abstract: Background:The skin produces cortisol by itself and regulates its own proliferation and differentiation. There is a possibility that topical corticosteroids (TCSs) influence the cortisol homeostasis in the skin.Aims and Objectives:The author described the density and distribution of cortisol and its parties in the epidermis after application of topical steroids immunohistologically.Materials and Methods:The forearm skin was biopsied before and after 2 weeks’ application of clobetasol propionate 0.05% two times… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Rapaport & Lebwohl proposed the mechanism for widespread erythema following TCS ceswww.medicaljournals.se/acta sation was secondary to the release of accumulated nitric oxide stores causing hyper-dilation of blood vessels (23) (TCSs suppress nitric oxide in the endothelium). Fukaya (24) proposed cortisol production by keratinocytes is suppressed by TCSs and so on cessation of TCSs there is relative cortisol insufficiency giving rise to some of the symptoms seen in TSW. It is possible disturbances at a cellular level -of which there may be several considering the multifactorial mode of action of TCSs -take considerable time to normalise.…”
Section: Discussionmentioning
confidence: 99%
“…Rapaport & Lebwohl proposed the mechanism for widespread erythema following TCS ceswww.medicaljournals.se/acta sation was secondary to the release of accumulated nitric oxide stores causing hyper-dilation of blood vessels (23) (TCSs suppress nitric oxide in the endothelium). Fukaya (24) proposed cortisol production by keratinocytes is suppressed by TCSs and so on cessation of TCSs there is relative cortisol insufficiency giving rise to some of the symptoms seen in TSW. It is possible disturbances at a cellular level -of which there may be several considering the multifactorial mode of action of TCSs -take considerable time to normalise.…”
Section: Discussionmentioning
confidence: 99%
“…Early cell models studies showed that exposure to glucocorticoids resulted in down-regulation of GR DNA and mRNA [50,51]. Subsequent studies have gone further to study variations in the two splicing variants of GR, the GRa and GRb isoform [52,53]. In 2009, Hagg [52] observed that following TCS treatment, patients with poor clinical response had upregulated GRb expression while this was unchanged in patients with good clinical response.…”
Section: Dysregulation Of Glucocorticoid Receptormentioning
confidence: 99%
“…He hypothesised that TCS application causes a decrease in self-production of cortisol by keratinocytes. However, a second study by Fukaya in 2017 showed an increase in cortisol staining in the epidermis with TCS application, followed by a decrease after cessation in a single healthy volunteer after 2 weeks of clobetasol propionate application [53]. The evidence for this thus remains unclear.…”
Section: Dysregulation Of Cortisol Production By Keratinocytesmentioning
confidence: 99%